Impact of Ischemic Cardiomyopathy on Right Ventricular Function using Speckle Tracking Echocardiography - Abdelmohsen Mostafa Aboualia (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Ischemic cardiomyopathy [ICM] refers to the reduced pumping ability of the heart due to damage of myocardium as a result of ischemia. Thus, early detection of coronary artery disease could save the myocardium. Speckle tracking emerged as a new diagnostic tool, but its role in ischemic cardiomyopathy is not well addressed. Aim of the work: To assess right ventricle [RV] function by two-dimensional [2D] speckle tracking imaging in patients with ICM. Patients and Methods: This study included 38 patients with ICM and 30 healthy subjects as a control group. Conventional echo-Doppler parameters of right ventricular function together with tissue Doppler imaging derived RV strain and speckle-tracking echo-derived RV global strain [STE-RVGST] were addressed. Results: The two groups were matched in age and sex. ICM had significantly higher values of LV Tei index [0.90±0.28] versus control group [0.51±0.13] with p value <0.001. Compared to control group, ischemic cardiomyopathy patients had significantly dilated right ventricular [RV] dimensions and volumes with impaired systolic and diastolic function. In this study RV tissue Doppler imaging [TDI] revealed statistically significant low Free Ea [6.76±2.72 versus 8.20±1.86], Free Sa [8.00±2.86 versus 10.91±1.10], TD-derived RV strain [19.83±15.19 versus 33.87±5.82] in ICM than control group. Speckle tracking derived global longitudinal strain was statistically lower in ICM [-10.01±3.7] versus -18.83±3.34 in control group. Conclusion: Patients with ischemic cardiomyopathy have both systolic and diastolic RV dysfunction, Speckle tracking echocardiography have an additive role in assessment of RV systolic dysfunction